A Review on Aggregation Approaches of Distributed Energy Resources - Tavares, Inês Vieira (Neutro à Terra, 2024)
With the increasing penetration of distributed energy resources (DER) into the grid, the power system has suffered some changes to become more sustainable, flexible, and cost-effective. For this reason, a need for new ways of operating the power system is emerging. The control of DER such as PV power, controllable load, demand response (DR) programs, energy storage units, and electric vehicles will facilitate their integration by balancing operations in the electricity grid. The increase of DER is stressing the distributed nature of power systems, in terms of equipment and in terms of management and control. So, new entities such as aggregators are acting as mediators between end- users and grid operators to facilitate the management and control of the power system. This paper makes a review of different aggregation approaches that can be applied for the integration of the DER in the electric power system, based on recent literature. It focuses on the role of DR aggregators, load aggregators, and energy storage aggregators, and the concepts related to each of these topics are covered.